What is addiction? - Ross, Don 1962-; Kincaid, Harold; Spurrett, David; Collins, Peter (MIT Press, 2010)
"The image of the addict in popular culture combines victimhood and moral failure; we sympathize with addicts in films and novels because of their suffering and their hard-won knowledge. And yet actual scientific knowledge about addiction tends to undermine this cultural construct. In What Is Addiction? leading addiction researchers from neuroscience, psychology, genetics, philosophy, economics, and other fields survey the latest findings in addiction science. They discuss such questions as whether addiction is one kind of condition, or several; if addiction is neurophysiological, psychological, or social, or incorporates aspects of all of these; to what extent addicts are responsible for their problems, and how this affects health and regulatory policies; and whether addiction is determined by inheritance or environment or both."--BOOK JACKET.